Various Police Language Terms in Sumenep Police: Sociolinguistic Perspective - Faruq Hidayat (Edumaspul: Jurnal Pendidikan, 2024)
This research is a qualitative descriptive that aims to describe the terms of the variety of police languages ​​at Polres Sumenep. This research theoretically used a sociolinguistic approach with research focused on the forms and meanings of the language varieties used in the police domain, especially at the Sumenep Police Station. Data collection in this study was conversant and semuka conversations. The results of this study indicate that the variety of police languages ​​has (1) acronym forms such as abribda, abribtu, bharaka, bharada, iptu, (2) abbreviation forms such as AKBP, AKP, TKP, DPO, BAP. The words of the various languages ​​in this study are (1) not experiencing a shift in meaning, (2) a small portion experiencing a shift in meaning narrowing.